In-vitro antioxidant activity of Cycas beddomei - Baggiya Selvi David,; Raja sundararajan, (International Journal of Phytomedicine, 2015)
The current study was to investigate antioxidant activity of methanol extract of whole plant of Cycas beddomei was administrated by utterly diverse models like DPPH radical scavenging assay, superoxide anion assay, nitric oxide radical inhibition assay, thiocyanate methodology, lipid peroxidation assay and hydroxyl radical scavenging assay. Methanol extract of Cycas beddomei showed effective antioxidant activity compared to straightforward antioxidants like ascorbic acid, rutin, curcumin, fat-soluble vitamin (Vitamin E) and α-tocopherol. The antioxidant activity depends upon the concentration and it had been increased with escalating the concentration of extract. The antioxidant activity could also be endorsed to the occurrence of phenolic and flavonoids compounds gift within the methanol extract. The results obtained within the present study point out that the methanol extract of whole plant of Cycas beddomei area unit a possible supply of natural antioxidant.